Tinjauan Sistem Informasi Ena Di Puskesmas Kecamatan Penjaringan Jakarta Utara - Haifa Pandhita Ayu; Noviandi Noviandi; Adi Widodo; Daniel Happy Putra (Syntax Corporation Indonesia, 2022)
The Penjaringan sub-district health center, North Jakarta, has implemented the ENA information system for all forms of data recording, medical records, and other health services. Problems that have often occurred in the ENA information system since 2017 are the system update process and the validation process. This study aimed to determine the application or function and Standard Operating Procedures of the ENA information system. The method used is qualitative with the type of descriptive research. Informants in this study were puskesmas officers with more than two years of service. The results showed that the ENA information system was good enough because it complied with the established Standard Operating Procedures. Some services on the ENA information system, such as the validation of the BPJS (P-Care) system, are not optimal because the validation process depends on the internet network provided. Internal training on the ENA information system needs to be carried out due to changes or developments in system features. Antivirus and network security need to be improved again for data security and reducing the risk of software damage that affects computer performance